2021
DOI: 10.26574/maedica.2021.16.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fall Risk in Elderly Rural Population

Abstract: Background: Fall risk assessment is an essential component of a comprehensive fall reduction and prevention program. Fall risk assessment is done to identify patients' risk for falls and ultimately prevent falls from occurring. The aim of the study was to identify the risk factors for fall in the elderly population.Methods: This study included 250 elderly patients > 60 years (105 males, 145 females) attending Medicine OPD in a tertiary care hospital. Detailed history including the previous h/o falls, medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…This is quite a high rate that needs to be addressed carefully given its untoward consequences on the elderly person and his/her family, as well as the whole community and health care system. Nonetheless, the rate is still lower than that reported by Geetha et al ( 12 ) in a study of fall risk in India who reported a rate 27.6%. This discrepancy might be due to that the Indian study was in a rural area, and the age of their participants was older in comparison with our study.…”
Section: Discussioncontrasting
confidence: 59%
“…This is quite a high rate that needs to be addressed carefully given its untoward consequences on the elderly person and his/her family, as well as the whole community and health care system. Nonetheless, the rate is still lower than that reported by Geetha et al ( 12 ) in a study of fall risk in India who reported a rate 27.6%. This discrepancy might be due to that the Indian study was in a rural area, and the age of their participants was older in comparison with our study.…”
Section: Discussioncontrasting
confidence: 59%
“…The number of risk factors raises the chance of falling in the elderly. [ 5 ] Assessment of fall risk in the elderly is performed by using functional assessment tools that assess important fall risk factors, including muscle strength, balance, functional mobility, and gait. Timed Up and Go test (TUG) assesses functional mobility and the Performance-Oriented Mobility Assessment test (POMA) assesses balance, postural control, and gait.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that compare the TUG and POMA against falls both separately and collectively have had mixed outcomes. [ 5 7 9 ] This study compares two simple scales, viz., TUG test and POMA test in fall prediction among elderly patients.…”
Section: Introductionmentioning
confidence: 99%